The Increasing Level of Comfort and Decreasing Blood Pressure of Hypertensive Elderly with “TERTARIK” (Terapi Tertawa dengan Musik Rindik) - Sari, Ni Luh Putu Dian Yunita; Martini, Ni Made Dwi Ayu (jitek, 2023)
Changes in people's activity patterns during the pandemic caused discomfort responses that had implications for blood pressure fluctuations in hypertensive elderly. This phenomenon is significant because high blood pressure can cause complications and hospitalisation. This study aimed to determine the effect of TERTARIK on the comfort level and blood pressure of hypertensive elderly. A quantitative approach with a quasi-experimental pre-post test design with a control group was chosen. The sampling technique was purposive sampling with inclusion and exclusion criteria. The sample size obtained was 64 (32 per group), and 2 in the intervention group dropped out. Data was collected for four weeks with an intervention frequency of once a week. Comfort level and blood pressure variables are not normally distributed. These variables were tested with the Wilcoxon for paired data and the Mann-Whitney for unpaired data. The results obtained were that there was an influence of TERTARIK intervention on the comfort level (p-value 0,001), systolic blood pressure (p-value 0.001, and diastolic blood pressure (0.001) for hypertensive elderly. These results can guide nursing care for hypertensive elderly, especially with the complementary approach.